2005
DOI: 10.1021/es050749f
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organic Pollutants in British Columbia Grizzly Bears:  Consequence of Divergent Diets

Abstract: A new method for chemical fingerprinting of petroleum biomakers is described. The method consists of GC-MS analysis, preprocessing of GC-MS chromatograms, and principal component analysis (PCA) of selected regions. The preprocessing consists of baseline removal by derivatization, normalization, and alignment using correlation optimized warping. The method was applied to chromatograms of m/z 217 (tricyclic and tetracyclic steranes) of oil spill samples and source oils. Oil spill samples collected from the coast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
118
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 59 publications
18
118
0
3
Order By: Relevance
“…Contaminant intake in marine mammals occurs primarily through food [42]. Divergent diet was shown to have profound effects on POP concentrations and patterns in grizzly bears (Ursus arctos horribilis) [43]. Similarly, differences in contaminant concentrations, patterns, and ratios have helped to elucidate diet composition of the three eastern North Pacific killer whale (Orcinus orca) ecotypes [37,44].…”
Section: Ecological and Biological Factors Affecting Contaminant Loadsmentioning
confidence: 99%
“…Contaminant intake in marine mammals occurs primarily through food [42]. Divergent diet was shown to have profound effects on POP concentrations and patterns in grizzly bears (Ursus arctos horribilis) [43]. Similarly, differences in contaminant concentrations, patterns, and ratios have helped to elucidate diet composition of the three eastern North Pacific killer whale (Orcinus orca) ecotypes [37,44].…”
Section: Ecological and Biological Factors Affecting Contaminant Loadsmentioning
confidence: 99%
“…In this sense, top predators are often suggested as ideal biomonitoring candidates as they integrate pollutant levels along food chains (Becker, 2003;Burger and Gochfeld, 2004;Cabana and Rasmussen, 1994;McIntyre and Beauchamp, 2007). Since contaminant emissions are not spatially uniform, top predators also become helpful integrators of the spatial distribution of pollutants, as many species have vast breeding ranges, are able to move freely at large scales and some of them even exploit resources ascribed to different ecosystems (Braune et al, 2005;Christensen et al, 2005;Hobson et al, 2004;Ricca et al, 2008;Roscales et al, 2010). However, there is a marked variability in these factors affecting the dynamics of contaminants throughout foodweb (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…BDE-209 is also present in biota including fish [7] and birds [8]. It has been demonstrated that bioaccumula-tion of BDE-209 occurred in terrestrial predators such as red fox [9] and British Columbia grizzly bears [10], and marine animals such as harbor seals [11]. Furthermore, BDE-209 has been detected in human blood and breast milk [12].…”
Section: Introductionmentioning
confidence: 99%